299 Validation of genomic evaluation on some economically important traits of Canadian purebred pigs. (7th December 2018) - Jafarikia, M; Sullivan, B; McSween, P; Maignel, L; Sullivan, B
Abstract: This study was performed to validate the accuracy of Genomic Estimated Breeding Values (GEBV) in comparison to traditional EBV calculation for prediction of future performance of pigs on some economically important traits. The traits studied were total number of piglets born (TPB), backfat thickness (BFT), growth rate (age to 100 kg live weight, AGE) and loin depth (adjusted to 100 kg live weight, LDP). Animals were genotyped with Illumina and Affymetrix high-density SNP panels and the number of remaining SNPs after the quality control and excluding the SNPs on the sex chromosomes were 44507, 45364 and 44967 for Duroc, Landrace, and Yorkshire pig breeds, respectively. All genotypes were imputed to the Illumina 70K SNP panel using the FImpute software. The gebv software was used to compute the GEBVs following the equivalent model of VanRaden. GEBVs of validation animals estimated before performance testing in September 2017 were correlated with the de-regressed national EBVs of March 2018 after performance testing. Except for AGE in Yorkshire and Landrace, the GEBV of September 2017 showed 12–63% higher correlation with adjusted phenotypes of March 2018 than September 2017 EBVs. The validation shows very promising results (Table 1) though there needs to be further investigation into the validation of AGE.